2011
DOI: 10.1159/000334360
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Density-Associated Changes in Clinicopathological Features of Minimal Change Nephrotic Syndrome in Adults

Abstract: Background: Differences in nephron number and/or glomerular size between individuals, in relation to intrauterine growth retardation or low birth weight, have been suggested to affect the clinical course of minimal change nephrotic syndrome (MCNS) in children. However, no previous study has investigated the potential influences of these histological variables on the clinical course of adult patients with MCNS. Methods: The glomerular density (GD; the number of non-sclerotic glomeruli per renal cortical area) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…A study in patients with minimal change disease found profile tubular density (number of tubules per area of cortex) to be correlated with glomerular density and inversely correlated with glomerular volume (14). We showed the same finding in kidney donors using the inverse measure, mean profile tubular area (area of cortex per tubule).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A study in patients with minimal change disease found profile tubular density (number of tubules per area of cortex) to be correlated with glomerular density and inversely correlated with glomerular volume (14). We showed the same finding in kidney donors using the inverse measure, mean profile tubular area (area of cortex per tubule).…”
Section: Discussionsupporting
confidence: 79%
“…In normal kidneys, the cortex consists only of nephrons and supporting vessels; increases in nephron size will disperse the glomeruli further apart, decreasing their density (11). Recent studies by Tsuboi et al found that larger glomerular volume, lower profile tubular density, and lower profile glomerular density were correlated and predictive of kidney failure and other outcomes in a variety of early glomerulopathies (12)(13)(14)(15). Conceptually, larger glomerular volume, lower profile tubular density (or larger mean profile tubular area), and lower glomerular density are all measures of larger nephron size (nephron hypertrophy).…”
Section: Introductionmentioning
confidence: 99%
“…63 Furthermore, Rule et al 64 indicated that the GD is associated with the kidney function and other metabolic characteristics, such as body mass index, hypertension and/or high-density lipoprotein cholesterol, based on the findings of renal biopsy samples in healthy adult kidney donors. 64 We also previously demonstrated that the individual value of the GD in renal tissue specimens obtained via percutaneous needle biopsy shows an approximately sevenfold variation in cases of IgA nephropathy (IgAN), 65,66 a fourfold variation in cases of membranous nephropathy (MN) 67 and a fourfold variation in cases of minimal change disease (MCD), 68 even in patients with a preserved renal function. In addition, a low GD on biopsy specimens is associated with a poor long-term renal prognosis and/or blunted response to corticosteroid therapy in these patients.…”
Section: Determining Factors Of the Nephron Numbermentioning
confidence: 96%
“…Besides, GD can serve as a response index to corticosteroids therapy in adult patients with kidney disease. 19 In this way, the treatment of corticosteroids in IgAN with eGFR of <50 ml/min per VALIGA study 21 and STOP-IgAN study. 22 Further prospective studies taking GD into account are needed to evaluate the benefit of corticosteroids in patients with a eGFR of <50 ml/min per 1.73 m 2 .…”
Section: -18mentioning
confidence: 99%